CircHECTD1 Regulates Cell Proliferation and Migration by the miR-320-5p/SLC2A1 Axis in Glioblastoma Multiform - Li, Wen; Wang, Shanshan; Shan, Boquan; Cheng, Xiang; He, Hui; Qin, Jianbing; Tang, Yi; Zhao, Heyan; Tian, Meiling; Zhang, Xinhua; Jin, Guohua (Frontiers in Oncology, 2021)
Glioblastoma multiform (GBM) is the most common and malignant primary brain cancer in adults, and thus, novel potential therapeutic targets for diagnosis and treatment are urgently needed. Circular RNAs (circRNAs) are a class of widespread and diverse endogenous RNAs that have been suggested as potential critical mediators during progression of various tumors. In this study, we investigated the involvement of circHECTD1 in GBM progression. CircHECTD1 Lentivirus, miR-320-5p mimic, and SLC2A1 Lentivirus were transduced into cancer cells independently or together. circHECTD1, miR-320-5p, and SLC2A1 level were detected by qRT-PCR. Western blot and qRT-PCR were applied to measure the expression of SLC2A1, CyclinD1, CDK2, and PCNA. Flow cytometry, EdU, colony formation, Transwell and wound-healing assays were conducted to assess cell proliferation and migration. Luciferase reporter assays were performed to determine the effect of miR-320-5p on circHECTD1 or SLC2A1. Xenograft experiments were implemented to evaluate tumor growth in vivo. CircHECTD1 expression led to the promotion of proliferation and migration of GBM cells. In addition, circHECTD1 acted as a ceRNA to interact with miR-320-5p, which targeted the solute carrier family 2 member 1 (SLC2A1). In vivo experiments also revealed that circHECTD1 promoted tumor growth. Collectively, our findings showed that the circHECTD1-miR-320-5p-SLC2A1 regulatory pathway promoted the progression of GBM, suggesting that circHECTD1 may be a therapeutic target for GBM.